Solar neutrinos observed by GALLEX at Gran Sasso - Anselmann, Peter; Hampel, W.; Heusser, G.; Kiko, J.; Kirsten, Till; Pernicka, Ernst; Plaga, R.; Rönn, U.; Sann, M.; Schlosser, Clemens; Wink, R.; Wójcik, M.; et al. (Physics letters, 1992)
We have measured the rate of production of 71Ge from 71Ga by solar neutrinos. The target consists of 30.3 t of gallium in the form of 8.13 M aqueous gallium chloride solution (101 t), shielded by ≈ 3300 m water equivalent of standard rock in the Gran Sasso Underground Laboratory (Italy). In nearly one year of operation, 14 measurements of the production rate of 71Ge were carried out to give, after corrections for side reactions and other backgrounds, an average value of 83 + 19 (stat.) ± 8 (syst.) SNU (1σ) due to solar neutrinos. This conclusion constitutes the first observation of solar pp neutrinos. Our result is consistent with the presence of the full pp neutrino flux expected according to the “standard solar model” together with a reduced flux of 8B + 7Be neutrinos as observed in the Homestake and Kamiokande experiments. Astrophysical reasons remain as a possible explanation of the solar neutrino problem. On the other hand, if the result is to be interpreted in terms of the MSW effect, it would fix neutrino masses and mixing angles within a very restricted range.
Elektronische Reproduktion der Druck-Ausgabe 16. Oktober 2002
Gesehen am 11.04.2023